Feedback and feedforward control in the context of model predictive control with application to the management of type 1 diabetes mellitus. (August 2019) - Goodwin, Graham C.; Seron, Maria M.
Abstract: A unified formulation of feedback and feedforward control is given in the context of model predictive control. The ideas are illustrated by the management of type 1 diabetes mellitus although the general principles apply, mutatis mutandis, to other scenarios and problems. Highlights: Unified formulation of feedback and feedforward control. Presented in the framework of model predictive control. Application to the management of type 1 diabetes mellitus (T1DM). In T1DM it is highly beneficial to measure disturbances to incorporate feedforward. Feedforward use for T1DM is sensitive to disturbance measurement and model accuracy.